The English spy - Silva, Daniel, 1960- (New York : Harper, an imprint of HarperCollinsPublishers, 2015)
She is an iconic member of the British Royal Family, beloved for her beauty and charitable works, resented by her former husband and his mother, the Queen of England. But when a bomb explodes aboard her holiday yacht, British intelligence turns to one man to track down her killer: legendary spy and assassin Gabriel Allon.
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Art restorers -- Fiction; Assassins -- Fiction; Suspense fiction; Spy stories